Facing Complaining Customer and Suppressed Emotion at Worksite Related to Sleep Disturbance in Korea - Lim, Sung-Shil; Lee, Wanhyung; Hong, Kwanyoung; Jeung, Dayee; Chang, Sei-Jin; Yoon, Jin-Ha (Journal of Korean medical science, 2016)
This study aimed to investigate the effect of facing complaining customer and suppressed emotion at worksite on sleep disturbance among working population. We enrolled 13,066 paid workers (male = 6,839, female = 6,227, age < 65 years) in the 3rd Korean Working Condition Survey (2011). The odds ratio (OR) and 95% confidence intervals (CI) for sleep disturbance occurrence were calculated using multiple logistic regression models. Among workers in working environments where they always engage complaining customers had a significantly higher risk for sleep disturbance than rarely group (The OR [95% CI]; 5.46 [3.43-8.68] in male, 5.59 [3.30-9.46] in female workers). The OR (95% CI) for sleep disturbance was 1.78 (1.16-2.73) and 1.63 (1.02-2.63), for the male and female groups always suppressing their emotions at the workplace compared with those rarely group. Compared to those who both rarely engaged complaining customers and rarely suppressed their emotions at work, the OR (CI) for sleep disturbance was 9.66 (4.34-20.80) and 10.17 (4.46-22.07), for men and women always exposed to both factors. Sleep disturbance was affected by interactions of both emotional demands (engaging complaining customers and suppressing emotions at the workplace). The level of emotional demand, including engaging complaining customers and suppressing emotions at the workplace is significantly associated with sleep disturbance among Korean working population.